Appreciative Inquiry, Can It Build a Sense of Community? - Rahma, Uslarika Hida; Zumaroh, Aprilia Siti (Psikostudia : Jurnal Psikologi, 2023)
Post-pandemic has a long-lasting impact on social organizations in a community. The involvement of members of social organizations is the primary factor that is highly required. In social organizations, a core value known as a sense of community is essential to ensuring the organization's long-term viability and promoting the active participation of all its constituent parts. This study aims to determine the effectiveness of appreciative inquiry in building a sense of community in organizations. A total of 30 participants from all social organizations in Malang Regency were involved in this study. Data analysis used the Paired Sample T-Test based on the pretest and post-test results. The results showed that the value of T = 3.092 > 1.701 with p = 0.000 <0.005 so that it can be interpreted that Appreciative Inquiry has a significant role in increasing the sense of community which can be shown by organizational members succeeding in designing organizational dreams and designing changes in the form of GOAT Strategy. The implementation of Appreciative Inquiry by the organization is expected to provide experience for members of social organizations so that they can develop the organization.Pasca pandemi memberikan efek jangka pada organisasi sosial di lingkungan masyarakat. Keterlibatan aktif anggota organisasi sosial menjadi hal utama yang sangat dibutuhkan. Sense of community dalam organisasi sosial merupakan core values yang harus dimiliki oleh anggota organisasi untuk menjaga keberlanjutan organisasi dan mendorong keterlibatan aktif seluruh komponen dalam organisasi. Penelitian ini bertujuan untuk mengetahui efektifitas Appreciative inquiry dalam membangun sense of community pada organisasi. Penelitian ini dilakukan pada seluruh anggota organisasi sosial di Kabupaten Malang dengan jumlah 30 peserta. Analisis data menggunakan Paired Sample T-Test. Hasil penelitian menunjukkan bahwa nilai T= 3,092 > 1,701 dengan p= 0,000 < 0,005 sehingga dapat diartikan bahwa Appreciative Inquiry memiliki peran signifikan terhadap peningkatkan sense of community yang dapat ditunjukkan dengan anggota organisasi berhasil merancang impian organisasi serta merancang perubahan berupa GOAT Strategy. Implementasi Appreciative Inquiry oleh organisasi diharapkan dapat memberikan pengalaman bagi anggota organisasi sosial sehingga mampu mengembangkan organisasi.